Positively charged composite nanofiltration membrane as well as preparation method and application thereof
By introducing a quaternary ammonium structure into the polyamide separation layer of the nanofiltration membrane, the positive charge repulsion effect is used to improve the retention effect of magnesium ions, and the problem of low separation efficiency of magnesium lithium in the existing nanofiltration membrane is solved, and high-efficiency magnesium Lithium is separated and suitable for large-scale production.
Patent Information
- Application Number
- CN202310974942.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
The existing nanofiltration membranes have low magnesium-lithium separation efficiency during the magnesium-lithium separation process, and the process conditions and raw materials are complex, making it difficult to achieve large-scale production.
Using a positively charged composite nanofiltration membrane, its polyamide separation layer contains a specific quaternary ammonium structure, which improves the retention effect of magnesium ions through the repulsion between positive charges. The preparation method includes preparing a porous support layer on the bottom layer, and The quaternary ammonium structure is formed by heat treatment and contacting haloalkanes.
While maintaining high water flux, the separation efficiency of magnesium lithium is significantly improved, which is suitable for applications in the field of water treatment and separation.
Smart Images

Figure CN119425422A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the membrane field, and in particular to a positively charged composite nanofiltration membrane and a preparation method and application thereof. Background Art
[0002] Lithium is the lightest metal in nature. It has the characteristics of high electrochemical activity, large specific heat capacity, good conductivity and ductility. It is widely used in many emerging industries and fields such as power batteries, energy storage, aerospace, controlled nuclear reactions, etc. It is called "white oil" and has important strategic and economic value. The battery industry accounts for about two-thirds of the terminal consumption of lithium resources. The electrification of transportation and energy storage have led to a continuous and rapid increase in the global demand for lithium resources. At present, with the widespread application of new energy vehicles in recent years, my country has become the world's largest consumer and trading country of lithium resources. As the demand for lithium energy continues to rise, the lithium extraction industry has also developed rapidly. In my country, most lithium resources are stored in salt lake brine. The current lithium extraction processes include precipitation, solar pond, extraction, calcination, membrane separation and adsorption. Due to the relatively high magnesium-lithium ratio in my country's salt lakes, most of the lithium extraction processes use a combination of adsorption and membrane separation.
[0003] At present, most of the nanofiltration membrane materials used for lithium extraction are made of polyamide. Its unique molecular structure determines that the membrane surface is negatively charged, and the interception rate of magnesium ions is low (less than 98%), so the magnesium-lithium separation coefficient is generally less than 20. In order to improve the magnesium-lithium separation coefficient of the nanofiltration membrane, researchers usually construct a positive charge modification layer on the surface of the nanofiltration membrane to improve the interception rate of the membrane to magnesium ions through the Donnan effect. CN114870629A discloses chelating metal ions on the surface of the nanofiltration membrane to improve the positive charge of the membrane surface, thereby improving the interception rate of the membrane to divalent metal ions. CN115105973A discloses branching ionic liquids on the surface of the nanofiltration membrane, and improving the positive charge of the membrane surface through amino cations in the ionic liquid. CN115770493A discloses a method for achieving efficient magnesium-lithium separation of nanofiltration membranes by controlling the pore size of the separation layer. However, the process conditions and raw materials of the above methods are relatively complex and cannot be achieved in large-scale production.
[0004] In short, whether it is to change the charge properties of the membrane surface or to change the pore size distribution of the membrane surface, it is of great significance to develop a nanofiltration membrane preparation technology suitable for industrial magnesium and lithium separation. Summary of the invention
[0005] The purpose of the present invention is to overcome the disadvantage of low magnesium-lithium separation efficiency of nanofiltration membranes in the prior art, and to provide a positively charged composite nanofiltration membrane and a preparation method and application thereof. The polyamide separation layer of the positively charged composite nanofiltration membrane contains a specific quaternary ammonium salt structure, so that the positively charged composite nanofiltration membrane has a high magnesium-lithium separation coefficient while maintaining a high water flux, and is particularly suitable for the field of water treatment separation.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a positively charged composite nanofiltration membrane, wherein the nanofiltration membrane comprises a bottom layer, a porous support layer and a polyamide separation layer stacked in sequence;
[0007] Wherein, the polyamide separation layer contains a quaternary ammonium salt structure represented by Formula I and / or Formula II;
[0008]
[0009] Wherein, X is a halogen; n is an integer of 0-10; and m is an integer of 2-10.
[0010] A second aspect of the present invention provides a method for preparing a positively charged composite nanofiltration membrane, wherein the preparation method comprises the following steps:
[0011] S1, preparing a porous supporting layer on the bottom layer;
[0012] S2, the membrane layer obtained in step S1 is first contacted with an aqueous phase of a polyamine containing a tertiary amine group, and is second contacted with an organic phase containing a polyacyl chloride, and after heat treatment, a composite nanofiltration membrane containing a polyamide separation layer is obtained;
[0013] S3, contacting the composite nanofiltration membrane with an organic solution containing halogenated alkanes and a catalyst, and drying to obtain the positively charged composite nanofiltration membrane.
[0014] The third aspect of the present invention provides a positively charged composite nanofiltration membrane prepared by the above preparation method.
[0015] A fourth aspect of the present invention provides an application of the positively charged composite nanofiltration membrane in the field of water treatment and separation.
[0016] Through the above technical scheme, the positively charged composite nanofiltration membrane provided by the present invention and its preparation method and application can achieve the following beneficial effects:
[0017] The polyamide separation layer of the positively charged composite nanofiltration membrane provided by the present invention contains a specific quaternary ammonium salt structure, which significantly improves the positive charge density of the composite nanofiltration membrane, and utilizes the repulsive effect between positive charges to improve the interception effect of the nanofiltration membrane on magnesium ions, thereby improving the magnesium-lithium separation efficiency of the nanofiltration membrane while maintaining a high water flux of the composite nanofiltration membrane.
[0018] In the preparation method of the positively charged composite nanofiltration membrane provided by the present invention, halogenated alkanes react biochemically with tertiary amines in a polyamide separation layer under the action of an alkaline catalyst, and the tertiary amines are converted into quaternary ammonium salt groups with positive charges. The repulsive effect between the positive charges improves the interception effect of the separation membrane on magnesium ions, thereby improving the magnesium-lithium separation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the reaction of ethyl bromide with the tertiary amine on the surface of the polyamide separation layer in Example 1 of the present invention;
[0020] Figure 2 This is the XPS spectrum of nitrogen atoms on the surface of the composite nanofiltration membrane in Comparative Example 1;
[0021] Figure 3 This is the XPS spectrum of nitrogen atoms on the surface of the positively charged composite nanofiltration membrane in Example 1;
[0022] Figure 4 This is the XPS spectrum of bromine atoms on the surface of the positively charged composite nanofiltration membrane in Example 1;
[0023] Figure 5 This is the XPS spectrum of surface nitrogen atoms of the composite nanofiltration membrane of Comparative Example 4. DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] The first aspect of the present invention provides a positively charged composite nanofiltration membrane, characterized in that the nanofiltration membrane comprises a bottom layer, a porous support layer and a polyamide separation layer stacked in sequence;
[0026] Wherein, the polyamide separation layer contains a quaternary ammonium salt structure represented by Formula I and / or Formula II;
[0027]
[0028] Wherein, X is a halogen; n is an integer of 0-10; and m is an integer of 2-10.
[0029] In the present invention, the polyamide separation layer of the positively charged composite nanofiltration membrane contains a specific quaternary ammonium salt structure, which significantly improves the positive charge density of the composite nanofiltration membrane. The repulsive effect between positive charges is used to improve the retention effect of the nanofiltration membrane on magnesium ions, thereby improving the magnesium-lithium separation efficiency of the nanofiltration membrane while maintaining a high water flux of the composite nanofiltration membrane.
[0030] In the present invention, * refers to the bonding position where the quaternary ammonium salt structure is connected to the polyamide separation layer.
[0031] Furthermore, X is Cl, Br or I.
[0032] Furthermore, n is an integer of 0-7; m is an integer of 2-8.
[0033] According to the present invention, the content of nitrogen atoms in the quaternary ammonium salt structure in the polyamide separation layer is 0.5 at.%-5 at.%.
[0034] In the present invention, when the content of nitrogen atoms in the quaternary ammonium salt structure in the polyamide separation layer meets the above range, it indicates that the content of quaternary ammonium salt groups in the positively charged composite nanofiltration membrane is relatively high, which can enable the positively charged composite nanofiltration membrane to have a higher surface positive potential.
[0035] Furthermore, the content of nitrogen atoms in the quaternary ammonium salt structure in the polyamide separation layer is 0.5 at.%-2.5 at.%.
[0036] According to the present invention, the surface Zeta potential of the nanofiltration membrane is -10 mV to 5 mV.
[0037] In the present invention, when the surface Zeta potential of the positively charged composite nanofiltration membrane satisfies the above range, it indicates that the composite nanofiltration membrane has a high surface electrode potential. When it is used for lithium-magnesium separation, it can better repel divalent magnesium ions, making it difficult for magnesium ions in the liquid to pass through the separation membrane, while allowing monovalent lithium ions to pass as much as possible, thereby obtaining a higher magnesium-lithium separation efficiency.
[0038] In the present invention, the surface Zeta potential of the nanofiltration membrane refers to the surface Zeta potential at pH=7.
[0039] Furthermore, the surface Zeta potential of the nanofiltration membrane is -7.5 mV to 5 mV.
[0040] According to the present invention, the average pore size of the nanofiltration membrane is 0.1-0.4 nm.
[0041] In the present invention, when the average pore size of the nanofiltration membrane meets the above range, it indicates that the positively charged composite nanofiltration membrane has a high density. When it is used for lithium-magnesium separation, it can better repel divalent magnesium ions, making it difficult for magnesium ions in the liquid to pass through the separation membrane, while allowing monovalent lithium ions to pass as much as possible, thereby obtaining a higher magnesium-lithium separation efficiency.
[0042] Furthermore, the average pore size of the nanofiltration membrane is 0.15-0.3 nm.
[0043] According to the present invention, the contact angle of the nanofiltration membrane is 40-60°.
[0044] In the present invention, when the contact angle of the nanofiltration membrane satisfies the above range, it indicates that the average pore size in the separation layer of the positively charged composite nanofiltration membrane is small and the pore distribution is narrow. At the same time, the surface of the positively charged composite nanofiltration membrane has high hydrophilicity, which can improve the retention rate of divalent metal ions while ensuring that the nanofiltration membrane has high water permeability.
[0045] Furthermore, the contact angle of the nanofiltration membrane is 40-50°.
[0046] In the present invention, the bottom layer and the porous support layer are not specifically limited, and can be made of various existing materials that have a certain strength and can be used for nanofiltration and reverse osmosis membranes.
[0047] In the present invention, the bottom layer is a non-woven fabric material, preferably polyester and / or polyethylene.
[0048] In the present invention, the porous support layer material may be at least one of polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone.
[0049] According to the present invention, the thickness of the bottom layer, the porous support layer, and the polyamide separation layer is not particularly limited, and can be a conventional choice in the art. However, in order to enable the three layers to play a better synergistic role, the obtained composite nanofiltration membrane can better have an excellent magnesium-lithium separation coefficient and a higher water flux. Preferably, the thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; the thickness of the polyamide separation layer is 10-500 nm, preferably 50-150 nm.
[0050] The second aspect of the present invention provides a method for preparing a positively charged composite nanofiltration membrane, characterized in that the preparation method comprises the following steps:
[0051] S1, preparing a porous supporting layer on the bottom layer;
[0052] S2, the membrane layer obtained in step S1 is first contacted with an aqueous phase of a polyamine containing a tertiary amine group, and is second contacted with an organic phase containing a polyacyl chloride, and after heat treatment, a composite nanofiltration membrane containing a polyamide separation layer is obtained;
[0053] S3, contacting the composite nanofiltration membrane with an organic solution containing halogenated alkanes and a catalyst, and drying to obtain the positively charged composite nanofiltration membrane.
[0054] In the present invention, the composite nanofiltration membrane is contacted with an organic solution containing halogenated alkanes and a catalyst. The halogenated alkanes react biochemically with the tertiary amine in the polyamide separation layer under the action of the catalyst, and the tertiary amine is converted into a quaternary ammonium salt group with a positive charge. The repulsive effect between the positive charges improves the interception effect of the separation membrane on magnesium ions, thereby improving the magnesium-lithium separation efficiency.
[0055] In the present invention, there is no particular limitation on the method for preparing the porous supporting layer on the bottom layer. It can be prepared by conventional methods in the art, preferably by a phase inversion method. Specifically, a polymer solution of the porous supporting layer material is coated on one surface of the bottom layer, and the porous supporting layer is obtained by phase inversion.
[0056] In the present invention, the phase inversion method can preferably be: dissolving the supporting layer polymer material in a solvent to obtain a polymer solution with a concentration of 10-20 weight %, and degassing at 20-40°C for 10-180min; then coating the polymer solution on the bottom layer to obtain an initial membrane, and then soaking it in water at a temperature of 10-30°C for 10-60min to obtain the supporting layer polymer porous membrane through the phase inversion layer.
[0057] The solvent may be N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, or the like.
[0058] According to the present invention, the polyamine containing a tertiary amine group is selected from at least one of polyethyleneimine, polyethylene polyamine, 1-aminopiperazine, 1,4-diaminopiperazine, 1,4-piperazine diethylamine and 1,4-bisaminopropylpiperazine. Preferably, the polyamine containing a tertiary amine group is 1,4-diaminopiperazine.
[0059] According to the present invention, the concentration of the polyamine containing tertiary amine groups in the aqueous phase of the polyamine containing tertiary amine groups is 0.1 wt%-10 wt%, preferably 0.5 wt%-2.5 wt%.
[0060] According to the present invention, the polyacid chloride is at least one selected from 1,3,5-benzenetricarboxylic acid chloride, 1,2-phthaloyl chloride, 1,3-phthaloyl chloride, 1,4-phthaloyl chloride and adipoyl chloride, preferably 1,3,5-phthaloyl chloride.
[0061] According to the present invention, the concentration of the polyacyl chloride in the organic phase containing the polyacyl chloride is 0.01 wt%-1 wt%, preferably 0.1 wt%-0.5 wt%.
[0062] According to the present invention, the amounts of the aqueous phase of the polyamine containing tertiary amine groups and the organic phase containing polyacid chlorides are such that the mass ratio of the polyamine containing tertiary amine groups to the polyacid chlorides is 0.1-10:1.
[0063] In the present invention, when the mass ratio of the polyamine containing tertiary amine groups to the polyacyl chloride is controlled to meet the above range, sufficient interfacial polymerization reaction between the polyamine containing tertiary amine groups and the polyacyl chloride can be ensured, thereby improving the crosslinking density of the prepared polyamide separation layer.
[0064] Furthermore, the amounts of the aqueous phase of the polyamine containing tertiary amine groups and the organic phase containing polyacid chlorides are such that the mass ratio of the polyamine containing tertiary amine groups to the polyacid chlorides is 0.5-5:1.
[0065] In the present invention, there is no particular limitation on the type of solvent in the organic phase containing polyacid chlorides, as long as it can dissolve the polyacid chlorides. Preferably, the solvent of the organic phase is one or more of n-hexane, dodecane, n-heptane, and alkane solvent oil (Isopar E, Isopar G, Isopar H, Isopar L, and Isopar M).
[0066] According to the present invention, there is no special limitation on the interfacial polymerization conditions of the polyamine containing tertiary amine groups and the polyacid chlorides, and the interfacial polymerization can be carried out according to the conventional conditions in the art. However, in order to enable the three layers to play a better synergistic role and enable the obtained composite nanofiltration membrane to better have an excellent magnesium-lithium separation coefficient and a higher water flux, preferably, the first contact time is 5-100s, preferably 10-60s; the second contact time is 10-200s, preferably 20-120s; the heat treatment conditions include: the heat treatment temperature is 40-150°C, preferably 50-120°C; the heat treatment time is 0.5-10min, preferably 1-5min.
[0067] In the present invention, in step S2, the ratio of the volume of the aqueous phase of the polyamine containing tertiary amine groups to the membrane area of the membrane layer obtained in step S1 is 0.05-1 mL / cm 2 , preferably 0.1-0.5 mL / cm 2 .
[0068] In the present invention, in step S2, the ratio of the volume of the organic phase containing polyacyl chloride to the membrane area of the membrane layer obtained in step S1 is 0.01-0.5 mL / cm 2 , preferably 0.05-0.25mL / cm 2 .
[0069] According to the present invention, in step S3, the halogenated alkane is selected from the halogenated alkane represented by formula III and / or the halogenated alkane represented by formula IV;
[0070]
[0071] wherein X1, X2 and X3 are each independently halogen; n is an integer of 0-10; and m is an integer of 2-10.
[0072] In the present invention, the use of halogenated alkanes having the above-mentioned specific structure can further increase the positive charge density on the surface of the positively charged composite nanofiltration membrane and further reduce the average pore size of the nanofiltration membrane.
[0073] Furthermore, X1, X2 and X3 are each independently Cl, Br or I; n is an integer of 0-7; and m is an integer of 2-8.
[0074] According to the present invention, the halogenated alkane is selected from methyl iodide, ethyl iodide, propyl iodide, butyl iodide, pentyl iodide, hexyl iodide, heptane iodide, octane iodide, nonane iodide, cyclopropane iodide, cyclobutane iodide, cyclopentane iodide, cycloheptane iodide, cyclooctane iodide, 1,2-diiodoethane, 1,3-diiodopropane, 1,4-diiodobutane, 1,5-diiodopentane, 1,6-diiodohexane, 1,7-diiodoheptane, 1,8-diiodooctane, methyl chloride, ethyl chloride, propyl chloride, butyl chloride, pentyl chloride, hexyl chloride, heptane iodide, octane iodide, nonane iodide, cyclopropane iodide, cyclobutane iodide, cyclopentane iodide, cycloheptane iodide, 1,8-diiodooctane, at least one of bromopropane, bromocyclopropane, bromocyclobutane, bromocyclopentane, bromocycloheptane, bromocyclooctane, 1,2-dibromoethane, 1,3-dichloropropane, 1,4-dichlorobutane, 1,5-dichloropentane, 1,6-dichlorohexane, 1,7-dichloroheptane, 1,8-dichlorooctane, methyl bromide, ethyl bromide, bromopropane, bromobutyl, bromopentane, bromohexane, bromoheptane, bromooctane, bromononane, bromodecane, bromocyclopropane, bromocyclobutane, bromocyclopentane, bromocycloheptane, bromocyclooctane, 1,2-dibromoethane, 1,3-dibromopropane, 1,4-dibromobutane, 1,5-dibromopentane, 1,6-dibromohexane, 1,7-dibromoheptane and 1,8-dibromooctane.
[0075] In the present invention, in order to ensure that the halogenated alkane can react with the residual amino group in the polyamide separation layer, preferably, the catalyst is an alkaline catalyst. Further, the catalyst is selected from at least one of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, potassium tert-butoxide and sodium tert-butoxide, preferably selected from sodium hydroxide and / or sodium tert-butoxide.
[0076] According to the present invention, the organic solution is an alcohol solvent. There is no particular limitation on the specific type of the alcohol solvent, for example, it can be one of methanol, ethanol, n-butanol and isopropanol, preferably methanol or ethanol.
[0077] According to the present invention, in step S3, the concentration of the halogenated alkane in the organic solution is 1 wt%-20 wt%.
[0078] In the present invention, when the concentration of the halogenated alkane in the organic solution in step S3 is controlled to meet the above range, it can ensure that the halogenated alkane is in full contact with the polyamide separation layer in the composite nanofiltration membrane, so that the tertiary amine on the surface of the polyamide separation layer can fully react with the halogenated alkane and have a high reaction efficiency, and ultimately the surface of the obtained positively charged composite nanofiltration membrane contains more quaternary ammonium salt groups.
[0079] Furthermore, in step S3, the concentration of the halogenated alkane in the organic solvent is 5wt%-10wt%.
[0080] According to the present invention, in the organic solution, the concentration of the catalyst is 0.01wt%-5wt%.
[0081] In the present invention, when the concentration of the catalyst in the organic solution in step S3 is controlled to meet the above range, it can ensure that the catalyst is in full contact with the halogenated alkane and the polyamide separation layer in the composite nanofiltration membrane, fully catalyze the reaction between the tertiary amine on the surface of the polyamide separation layer and the halogenated alkane, and improve the reaction efficiency between the two, so that the surface of the obtained positively charged composite nanofiltration membrane contains more quaternary ammonium salt groups.
[0082] Furthermore, in step S3, the concentration of the catalyst in the organic solvent is 0.1wt%-1wt%.
[0083] According to the present invention, the ratio of the volume of the organic solution to the membrane area of the composite nanofiltration membrane is 0.1-1 mL / cm 2 .
[0084] In the present invention, by controlling the volume of the organic solution and the membrane area of the composite nanofiltration membrane to meet the above range, it is possible to ensure that the tertiary amine atoms in the polyamide separation layer are converted into quaternary ammonium salt groups to the maximum extent, thereby increasing the positive potential of the membrane surface and improving the retention rate of the composite nanofiltration membrane for divalent metal ions.
[0085] Furthermore, the ratio of the volume of the organic solution to the membrane area of the composite nanofiltration membrane is 0.2-0.5 mL / cm 2 .
[0086] According to the present invention, the contact conditions include: the contact time is 1-120 minutes.
[0087] In the present invention, when the contact time between the composite nanofiltration membrane and the organic solution containing the halogenated alkane and the catalyst is controlled to meet the above range, it can ensure that the halogenated alkane and the tertiary amine remaining on the surface of the polyamide separation layer fully react, and the two have a high reaction efficiency, so that the surface of the obtained positively charged composite nanofiltration membrane contains more quaternary ammonium salt groups.
[0088] Furthermore, the contact conditions include: the contact time is 5-60 minutes.
[0089] In the present invention, there is no particular limitation on the contact temperature, and it may be, for example, room temperature (20-30° C.).
[0090] According to the present invention, the drying conditions include: drying temperature of 30-80° C.; drying time of 0.5-5 min.
[0091] Furthermore, the drying conditions include: drying temperature of 40-60° C.; drying time of 1-3 min.
[0092] The third aspect of the present invention provides a positively charged composite nanofiltration membrane prepared by the above preparation method.
[0093] A fourth aspect of the present invention provides an application of the positively charged composite nanofiltration membrane in the field of water treatment and separation.
[0094] Other features and advantages of the present invention will be described in detail in the following detailed description.
[0095] The present invention will be described in detail below by way of examples. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.
[0096] In the following examples and comparative examples:
[0097] (1) The water flux of the positively charged composite nanofiltration membrane is tested by the following method: the nanofiltration membrane is placed in a membrane pool, and the water permeation of the composite nanofiltration membrane in a certain period of time is measured under the conditions of 0.5 MPa and a temperature of 25°C, and the water flux is calculated by the following formula:
[0098] J = Q / (A·t), where J is the water flux, Q is the water permeation (L), and A is the effective membrane area of the composite nanofiltration membrane (m 2 ), t is time (h).
[0099] (2) The desalination rate of the positively charged composite nanofiltration membrane was tested by the following method: the nanofiltration membrane was placed in a membrane pool, the original aqueous solution was 2000 ppm magnesium chloride or 2000 ppm lithium chloride, and after pre-pressing at 0.2 MPa for 0.5 h, the permeate was obtained at a pressure of 0.5 MPa, the concentrations of magnesium chloride and lithium chloride in the permeate were measured by ion chromatography, and the desalination rate was calculated by the following formula:
[0100] R=(C f -C p ) / C f ×100%, where R is the desalination rate, C f is the concentration of magnesium chloride or lithium chloride in the original solution (measured by conductivity meter), C pIt is the concentration of magnesium chloride or lithium chloride in the permeate (measured by conductivity meter).
[0101] (3) The magnesium-lithium separation coefficient of the positively charged composite nanofiltration membrane was tested by the following method: the nanofiltration membrane was placed in a membrane pool, the original aqueous solution was a mixture of 2000 ppm magnesium chloride and 100 ppm lithium chloride, and after pre-pressing at 0.2 MPa for 0.5 h, the permeate was obtained at a pressure of 0.5 MPa.
[0102] The magnesium-lithium separation coefficient is calculated by the following formula:
[0103] Where S is the magnesium-lithium separation coefficient, C Li,p and C Li,f are the concentrations of lithium ions in the permeate and raw material solution (measured by ion chromatography); C Mg,p and C Mg,f are the concentrations of magnesium ions in the permeate and raw solution (measured by ion chromatography), respectively.
[0104] (4) The nitrogen atom content in the quaternary ammonium salt structure in the positively charged composite nanofiltration membrane is measured by the following method:
[0105] Before the measurement, the nanofiltration membrane was dried in an oven to constant weight, and the elemental composition of the nanofiltration membrane surface was determined using a SigmaProbe X-ray photoelectron spectrometer produced by Thermo VG, UK. The content of nitrogen atoms in the quaternary ammonium salt structure in the polyamide separation layer was calculated using the following formula:
[0106]
[0107] Among them, A N + Represents the peak area of nitrogen atoms in the quaternary ammonium salt group in the XPS spectrum ( Figure 3 The peak area at the middle bond energy of 403 eV); A N represents the peak area of nitrogen atoms in the separation layer in the XPS spectrum ( Figure 3 The sum of the peak areas at 403eV and 399eV in N represents the atomic content (at.%) of nitrogen atoms in the polyamide separation layer.
[0108] (5) Average pore size test of positively charged composite nanofiltration membrane: measured by PEG solute transfer method, the detailed steps are as follows:
[0109] (i) Testing the retention rate of nanofiltration membranes for PEG with different molecular sizes;
[0110] (ii) Linear fitting was performed between PEG size and retention rate in a logarithmic-probability coordinate system, and the PEG size corresponding to 50% retention rate was the average pore size of the separation membrane.
[0111] (6) Surface Zeta potential test of positively charged composite nanofiltration membrane: The test was carried out using a Surpass electrokinetic analyzer (Anton Paar), the circulating fluid was a dilute KCl aqueous solution, and the pH of the test fluid was 7.
[0112] (7) Contact angle of positively charged composite nanofiltration membrane: The surface contact angle of the composite membrane sample was tested using the sessile drop method using a DSA100 surface contact angle meter produced by KRUSS, Germany. Before the test, the sample was dried in a 60°C vacuum oven for 30 min to remove surface and internal moisture. The dried membrane was then attached to a flat glass slide with double-sided tape. The volume of each water drop was 2 μL. The water drop was dropped on the membrane surface for 3 s before being tested. The final contact angle was determined by taking the average value after multiple measurements.
[0113] (8) The thickness of each layer in the positively charged composite nanofiltration membrane was measured using a spiral micrometer and a scanning electron microscope.
[0114] In addition, in the following examples and comparative examples:
[0115] Aminopiperazine, 1,4-diaminopiperazine, 1,4-piperazinediethylamine, 1,3,5-benzenetricarboxylic acid chloride, propyl chloride, ethyl bromide, methyl iodide, 1,6-dichlorohexane, 1,6-dibromohexane and 1,6-diiodohexane were all purchased from J&K Technology Co., Ltd., and other chemical reagents were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0116] The supporting layer is prepared by a phase inversion method, and the specific steps are as follows:
[0117] A certain amount of polysulfone (number average molecular weight of 80000 g / mol) was dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 18 wt%, and degassed at 25°C for 120 min; then, the polysulfone solution was coated on a polyester non-woven fabric (with a thickness of 75 μm) using a scraper to obtain an initial membrane, which was then immersed in water at a temperature of 25°C for 60 min to allow the polysulfone layer on the surface of the polyester non-woven fabric to undergo phase transformation into a porous membrane, and finally washed with water three times to obtain a bottom layer-porous support layer with a total thickness of 115 μm.
[0118] Comparative Example 1
[0119] The above area is 400cm 2The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 0.5 wt% of 1,4-diaminopiperazine, and the liquid was drained after contacting at 25°C for 60 seconds; then, the upper surface of the support layer was contacted with 25 mL of an Isopar E solution containing 0.1 wt% of 1,3,5-benzenetricarboxylic acid chloride, and the liquid was drained after contacting at 25°C for 60 seconds; then, the membrane was placed in an oven and heated at 70°C for 3 minutes to obtain a composite nanofiltration membrane D1. Among them, the mass ratio of 1,4-diaminopiperazine to 1,3,5-benzenetricarboxylic acid chloride is 10:1.
[0120] Comparative Example 2
[0121] The above area is 400cm 2 The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 0.5 wt% 1,4-piperazine diethylamine, and the solution was drained after contacting at 25°C for 60 seconds; then, the upper surface of the support layer was contacted with 25 mL of an Isopar E solution containing 0.1 wt% 1,3,5-benzenetricarboxylic acid chloride, and the solution was drained after contacting at 25°C for 60 seconds; then, the membrane was placed in an oven and heated at 70°C for 3 minutes to obtain a composite nanofiltration membrane D2. Among them, the mass ratio of 1,4-piperazine diethylamine to 1,3,5-benzenetricarboxylic acid chloride was 10:1.
[0122] Comparative Example 3
[0123] The above area is 400cm 2 The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 0.5 wt% 1-aminopiperazine, and the liquid was drained after contacting at 25°C for 60 seconds; then, the upper surface of the support layer was contacted with 25 mL of an Isopar E solution containing 0.1 wt% 1,3,5-benzenetricarboxylic acid chloride, and the liquid was drained after contacting at 25°C for 60 seconds; then, the membrane was placed in an oven and heated at 70°C for 3 minutes to obtain a composite nanofiltration membrane D3. Among them, the mass ratio of 1-aminopiperazine to 1,3,5-benzenetricarboxylic acid chloride is 10:1.
[0124] Example 1
[0125] (1) The above area is 400cm 2 The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 0.5 wt% of 1,4-diaminopiperazine, and the liquid is drained after contacting at 25°C for 60 seconds; then, the upper surface of the support layer is contacted with 25 mL of an Isopar E solution containing 0.1 wt% of 1,3,5-benzenetricarboxylic acid chloride, and the liquid is drained after contacting at 25°C for 60 seconds; then, the membrane is placed in an oven and heated at 70°C for 3 minutes to obtain a composite nanofiltration membrane. Among them, the mass ratio of 1,4-diaminopiperazine to 1,3,5-benzenetricarboxylic acid chloride is 10:1.
[0126] (2) The obtained composite nanofiltration membrane was immersed in 200 mL of a methanol solution containing 10 wt % ethyl bromide and 0.5 wt % sodium tert-butoxide. After 30 min, the membrane was taken out and dried at 50° C. for 1 min to obtain a positively charged composite nanofiltration membrane N1.
[0127] Figure 1 Schematic diagram of the reaction of ethyl bromide with the tertiary amine on the surface of the polyamide separation layer in the composite nanofiltration membrane in Example 1; specifically, ethyl bromide reacts electrophilically with the residual tertiary amine in the polyamide separation layer to generate a quaternary ammonium salt structure.
[0128] Figure 2 This is the XPS spectrum of the surface nitrogen atoms of the composite nanofiltration membrane of Comparative Example 1, Figure 3 The XPS spectrum of the surface nitrogen atoms of the positively charged composite nanofiltration membrane of Example 1 is shown in FIG. Figure 2 and Figure 3 It can be seen that a new signal peak appears at 401 eV (red line), which corresponds to the signal of the nitrogen atom of the quaternary ammonium salt, indicating that ethyl bromide reacts with the tertiary amine in the polyamide separation layer to form a quaternary ammonium salt structure.
[0129] Figure 4 The XPS spectrum of the surface bromine atoms of the positively charged composite nanofiltration membrane of Example 1 is shown in FIG. Figure 4 It can be found that the signal peak corresponding to the counter ion bromine of the positively charged quaternary ammonium salt appears at 67-69 eV, indicating that the quaternary ammonium salt group is successfully modified onto the polyamide separation layer of the nanofiltration membrane.
[0130] Example 2
[0131] (1) The above area is 400cm 2 The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 0.5 wt% of 1,4-piperazine diethylamine, and the liquid is drained after contacting at 25°C for 60 seconds; then, the upper surface of the support layer is contacted with 25 mL of an Isopar E solution containing 0.1 wt% of 1,3,5-benzenetricarboxylic acid chloride, and the liquid is drained after contacting at 25°C for 60 seconds; then, the membrane is placed in an oven and heated at 70°C for 3 minutes to obtain a composite nanofiltration membrane. Among them, the mass ratio of 1,4-piperazine diethylamine to 1,3,5-benzenetricarboxylic acid chloride is 10:1.
[0132] (2) The obtained composite nanofiltration membrane was immersed in 200 mL of a methanol solution containing 5 wt % of chloropropane and 0.5 wt % of potassium hydroxide for 1 min, then taken out and dried at 50° C. for 1 min to obtain a quaternary ammonium salt-modified positively charged composite nanofiltration membrane N2.
[0133] Example 3
[0134] (1) The above area is 400cm 2The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 0.5 wt% of 1-aminopiperazine, and the liquid is drained after contacting at 25°C for 60 seconds; then, the upper surface of the support layer is contacted with 25 mL of an Isopar E solution containing 0.1 wt% of 1,3,5-benzenetricarboxylic acid chloride, and the liquid is drained after contacting at 25°C for 60 seconds; then, the membrane is placed in an oven and heated at 70°C for 3 minutes to obtain a composite nanofiltration membrane. Among them, the mass ratio of 1-aminopiperazine to 1,3,5-benzenetricarboxylic acid chloride is 10:1.
[0135] (2) The obtained composite nanofiltration membrane was immersed in 200 mL of a methanol solution containing 10 wt % iodomethane and 0.5 wt % potassium hydroxide for 1 min, then taken out and dried at 50° C. for 1 min to obtain a positively charged composite nanofiltration membrane N3.
[0136] Example 4
[0137] The preparation method is the same as that in Example 1, except that in step (2), 1,6-dibromohexane is used instead of ethyl bromide to prepare the positively charged composite nanofiltration membrane N4.
[0138] Example 5
[0139] The preparation method is the same as that in Example 1, except that in step (2), 1,6-diiodohexane is used instead of ethyl bromide to prepare the positively charged composite nanofiltration membrane N5.
[0140] Example 6
[0141] The preparation method is the same as that in Example 1, except that in step (2), 1,6-dichlorohexane is used instead of ethyl bromide to prepare the positively charged composite nanofiltration membrane N6.
[0142] Example 7
[0143] The preparation method is the same as that in Example 1, except that in step (2), a mixed solution of 1,6-diiodohexane and methyl iodide is used to replace the ethyl bromide solution, wherein the concentrations of 1,6-diiodohexane and methyl iodide are both 5% by weight, to obtain a positively charged composite nanofiltration membrane N7.
[0144] Example 8
[0145] The preparation method is the same as that in Example 1, except that in step (2), the concentration of ethyl bromide is 1% by weight, and a positively charged composite nanofiltration membrane N8 is obtained.
[0146] Example 9
[0147] The preparation method is the same as that in Example 1, except that in step (2), the concentration of ethyl bromide is 20% by weight, to obtain a positively charged composite nanofiltration membrane N9.
[0148] Example 10
[0149] The preparation method is the same as that in Example 1, except that in step (2), the concentration of ethyl bromide is 0.1% by weight, to obtain a positively charged composite nanofiltration membrane N10.
[0150] Embodiment 11
[0151] The preparation method is the same as that in Example 1, except that in step (2), the concentration of ethyl bromide is 30% by weight, to obtain a positively charged composite nanofiltration membrane N11.
[0152] Comparative Example 4
[0153] The preparation method is the same as that of Example 1, except that in step (1), 1,4-cyclohexanediamine is used instead of 1,4-diaminopiperazine to obtain a composite nanofiltration membrane D4.
[0154] Figure 5 The XPS spectrum of the surface nitrogen atoms of the composite nanofiltration membrane of Comparative Example 4 is shown in FIG. Figure 5 It can be seen that there is no signal peak of the quaternary ammonium salt group at around 400 eV, indicating that in this invention, only the tertiary amine group present in the separation layer can be converted into the quaternary ammonium salt group through chemical reaction.
[0155] The thickness, surface Zeta potential, average pore size, nitrogen atom content in the quaternary ammonium salt structure in the polyamide separation layer, and contact angle of each layer of the composite membrane in the examples and comparative examples are shown in Table 1.
[0156] Table 1
[0157]
[0158] a It refers to the content of nitrogen atoms in the quaternary ammonium salt structure in the polyamide separation layer.
[0159] It can be seen from Table 1 that after the composite nanofiltration membrane is contacted with an organic solution containing halogenated alkanes and a catalyst, the halogenated alkanes react biochemically with the tertiary amine in the polyamide separation layer under the action of the catalyst, and the tertiary amine is converted into a quaternary ammonium salt group with a positive charge. The quaternary ammonium salt group increases the positive potential on the surface of the nanofiltration membrane and increases the hydrophilicity; after the halogenated alkanes modify the polyamide separation layer, the average pore size of the nanofiltration membrane separation layer decreases, indicating that after the alkyl chain of the halogenated alkanes is modified to the polyamide separation layer, the free volume between the molecules is reduced.
[0160] It can be seen from Comparative Example 4 that only when the polyamide separation layer contains tertiary amine groups can quaternary ammonium salt groups be generated on the surface of the polyamide through a chemical reaction with alkyl halides.
[0161] The water flux, MgCl2 desalination rate, LiCl desalination rate and magnesium-lithium separation factor of the composite membrane of the embodiment and the comparative example were tested, and the results are shown in Table 2.
[0162] Table 2
[0163]
[0164]
[0165] As can be seen from Table 2, halogenated alkanes react with tertiary amines in the polyamide separation layer under the action of alkaline catalysts, and the tertiary amines are converted into quaternary ammonium salt structures with positive charges. The rejection effect of the composite nanofiltration membrane for magnesium ions is improved through the repulsive effect between positive charges, thereby improving the magnesium-lithium separation efficiency (Table 2). On the other hand, after the halogenated alkanes are branched, the pores between the molecules of the polyamide separation layer are reduced (Table 1), and the rejection rate of the composite nanofiltration membrane for salt ions is improved. At the same time, the quaternary ammonium salt increases the hydrophilicity of the composite nanofiltration membrane and increases the water flux of the composite nanofiltration membrane. After the dihalogenated alkanes react with the tertiary amine groups on the surface of the composite nanofiltration membrane, a secondary cross-linking structure is formed, the membrane pores are further reduced (Table 1), and the salt rejection of the membrane is further improved.
[0166] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A positively charged composite nanofiltration membrane, characterized in that: The nanofiltration membrane comprises a bottom layer, a porous support layer and a polyamide separation layer stacked in sequence; Wherein, the polyamide separation layer contains a quaternary ammonium salt structure represented by Formula I and / or Formula II; Wherein, X is a halogen; n is an integer of 0-10; and m is an integer of 2-10.
2. The positively charged composite nanofiltration membrane according to claim 1, wherein: X is Cl, Br or I; Preferably, n is an integer of 0-7; and m is an integer of 2-8.
3. The positively charged composite nanofiltration membrane according to claim 1 or 2, wherein: The content of nitrogen atoms in the quaternary ammonium salt structure in the polyamide separation layer is 0.5 at.%-5 at.%, preferably 0.5 at.%-2.5 at.%.
4. The positively charged composite nanofiltration membrane according to any one of claims 1 to 3, wherein: The surface Zeta potential of the nanofiltration membrane is -10 mV to 5 mV, preferably -7.5 mV to 5 mV.
5. The positively charged composite nanofiltration membrane according to any one of claims 1 to 4, wherein: The average pore size of the nanofiltration membrane is 0.1-0.4 nm, preferably 0.15-0.3 nm.
6. The positively charged composite nanofiltration membrane according to any one of claims 1 to 5, wherein: The contact angle of the nanofiltration membrane is 40-60°, preferably 40-50°.
7. The positively charged composite nanofiltration membrane according to any one of claims 1 to 6, wherein: The thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; Preferably, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; Preferably, the thickness of the polyamide separation layer is 10-500 nm, preferably 50-150 nm.
8. A method for preparing a positively charged composite nanofiltration membrane, characterized in that: The preparation method comprises the following steps: S1, preparing a porous supporting layer on the bottom layer; S2, the membrane layer obtained in step S1 is first contacted with an aqueous phase of a polyamine containing a tertiary amine group, and is second contacted with an organic phase containing a polyacyl chloride, and after heat treatment, a composite nanofiltration membrane containing a polyamide separation layer is obtained; S3, contacting the composite nanofiltration membrane with an organic solution containing halogenated alkanes and a catalyst, and drying to obtain the positively charged composite nanofiltration membrane.
9. The preparation method according to claim 8, wherein: In step S2, the polyamine containing a tertiary amine group is selected from at least one of polyethyleneimine, polyethylene polyamine, 1-aminopiperazine, 1,4-diaminopiperazine, 1,4-piperazine diethylamine and 1,4-bisaminopropylpiperazine; Preferably, the concentration of the polyamine containing tertiary amine groups in the aqueous phase of the polyamine containing tertiary amine groups is 0.1wt%-10wt%, preferably 0.5wt%-2.5wt%; Preferably, the polyacid chloride is selected from at least one of 1,3,5-benzene trimethylene dicarboxylic acid chloride, 1,2-phthaloyl dicarboxylic acid chloride, 1,3-phthaloyl dicarboxylic acid chloride, 1,4-phthaloyl dicarboxylic acid chloride and adipoyl dicarboxylic acid chloride; Preferably, the concentration of the polyacyl chloride in the organic phase containing the polyacyl chloride is 0.01wt%-1wt%, preferably 0.1wt%-0.5wt%; Preferably, the amount of the aqueous phase of the polyamine containing tertiary amine groups and the organic phase containing polyacid chlorides is such that the mass ratio of the polyamine containing tertiary amine groups to the polyacid chlorides is 0.1-10:1, preferably 0.5-5:1; Preferably, the first contact time is 5-100 s, preferably 10-60 s; Preferably, the second contact time is 10-200s, preferably 20-120s; Preferably, the heat treatment conditions include: heat treatment temperature of 40-150° C., preferably 50-120° C.; heat treatment time of 0.5-10 min, preferably 1-5 min.
10. The preparation method according to claim 8 or 9, wherein: In step S3, the halogenated alkane is selected from the halogenated alkane represented by formula III and / or the halogenated alkane represented by formula IV; wherein X1, X2 and X3 are each independently halogen; n is an integer of 0-10, and m is an integer of 2-10; Preferably, the halogenated alkane is selected from methyl iodide, ethyl iodide, propyl iodide, butyl iodide, pentyl iodide, hexyl iodide, heptane iodide, octane iodide, nonane iodide, cyclopropane iodide, cyclobutane iodide, cyclopentane iodide, cycloheptane iodide, cyclooctane iodide, 1,2-diiodoethane, 1,3-diiodopropane, 1,4-diiodobutane, 1,5-diiodopentane, 1,6-diiodohexane, 1,7-diiodoheptane, 1,8-diiodooctane, methyl chloride, ethyl chloride, propyl chloride, butyl chloride, pentyl chloride, hexyl chloride, heptane iodide, octane iodide, nonane iodide, cyclopropane iodide, cyclobutane iodide, cyclopentane iodide, cycloheptane iodide, , at least one of chlorocyclooctane, 1,2-dichloroethane, 1,3-dichloropropane, 1,4-dichlorobutane, 1,5-dichloropentane, 1,6-dichlorohexane, 1,7-dichloroheptane, 1,8-dichlorooctane, methyl bromide, ethyl bromide, bromopropane, bromobutyl, bromopentane, bromohexane, bromoheptane, bromooctane, bromononane, bromodecane, bromocyclopropane, bromocyclobutane, bromocyclopentane, bromocycloheptane, bromocyclooctane, 1,2-dibromoethane, 1,3-dibromopropane, 1,4-dibromobutane, 1,5-dibromopentane, 1,6-dibromohexane, 1,7-dibromoheptane and 1,8-dibromooctane; Preferably, the catalyst is selected from at least one of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, potassium tert-butoxide and sodium tert-butoxide, preferably selected from sodium hydroxide and / or sodium tert-butoxide; Preferably, the organic solution is an alcohol solvent.
11. The preparation method according to any one of claims 8 to 10, wherein: In step S3, in the organic solution, the concentration of the halogenated alkane is 1wt%-20wt%, preferably 5-10wt%; Preferably, in the organic solution, the concentration of the catalyst is 0.01wt%-5wt%, preferably 0.1wt%-1wt%; Preferably, the ratio of the volume of the organic solution to the membrane area of the composite nanofiltration membrane is 0.1-1 mL / cm 2 ; Preferably, the contact conditions include: contact time is 1-120 min, preferably 5-60 min; Preferably, the drying conditions include: drying temperature of 30-80°C, preferably 40-60°C; drying time of 0.5-5 min, preferably 1-3 min.
12. A positively charged composite nanofiltration membrane prepared by the preparation method according to any one of claims 8 to 11.
13. Use of the positively charged composite nanofiltration membrane according to any one of claims 1 to 7 and 12 in the field of water treatment and separation.
Citation Information
Patent Citations
High-selectivity nanofiltration membrane as well as preparation method and application thereof
CN114870629A
Preparation method and application of nanofiltration membrane for efficient magnesium-lithium separation
CN115105973A
Narrow-aperture magnesium-lithium separation nanofiltration membrane and preparation method thereof
CN115770493A
Positively charged nano-filtration membrane based on tertiary amine type amphiphilic copolymer and preparation method thereof
CN105642129A
Preparation method of acid-resistant poly(amide-triazine-amine) nanofiltration composite membrane
CN107930412A